2014
DOI: 10.1289/ehp.1307473
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Postnatal Serum PCB Concentrations and Cochlear Function in Children at 45 Months of Age

Abstract: Background: Some experimental and human data suggest that exposure to polychlorinated biphenyls (PCBs) may induce ototoxicity, though results of previous epidemiologic studies are mixed and generally focus on either prenatal or postnatal PCB concentrations exclusively.Objectives: Our aim was to evaluate the association between pre- and postnatal PCB concentrations in relation to cochlear status, assessed by distortion product otoacoustic emissions (DPOAEs), and to further clarify the critical periods in develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 44 publications
3
45
1
Order By: Relevance
“…We have previously reported adverse effects attributed to postnatal PCB exposure on neurophysiological and cognitive measures in the same cohort of children (Boucher et al 2011, 2012b; Saint-Amour et al 2006). Interestingly, in a recent birth-cohort study conducted in Eastern Slovakia, postnatal PCB exposure, but not prenatal exposure, was associated with impaired cochlear function in 45-month old children as revealed by distortion product otoacoustic emissions (Jusko et al, 2014). These findings contrast with a large majority of PCB studies, which have concluded that neurodevelopmental effects in children are uniquely observed with prenatal rather than postnatal exposure (e.g., Jacobson and Jacobson 1996; 2003; Forns et al 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported adverse effects attributed to postnatal PCB exposure on neurophysiological and cognitive measures in the same cohort of children (Boucher et al 2011, 2012b; Saint-Amour et al 2006). Interestingly, in a recent birth-cohort study conducted in Eastern Slovakia, postnatal PCB exposure, but not prenatal exposure, was associated with impaired cochlear function in 45-month old children as revealed by distortion product otoacoustic emissions (Jusko et al, 2014). These findings contrast with a large majority of PCB studies, which have concluded that neurodevelopmental effects in children are uniquely observed with prenatal rather than postnatal exposure (e.g., Jacobson and Jacobson 1996; 2003; Forns et al 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…PCBs readily cross the mammalian placenta and are mobilized from body fat into breast milk during lactation, putting the developing offspring at risk (Jacobson et al 1984). One cause for concern is that developmental exposure to PCBs has been associated with long-lasting hearing deficits in animal models and humans (Crofton et al 2000; Goldey et al 1995; Jusko et al, 2014; Poon et al 2011; Powers et al 2006; Trnovec et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…An interesting factor to consider is that all three of these contaminants have been associated with subtle deficits in hearing and/or auditory processing (e.g. Osman et al, 1999; Rice and Gilbert, 1992; Jusko et al, 2014). This suggests there could be a complex interplay whereby subtle deficits in auditory function impair language development resulting in deficits in overall cognitive function, and verbal abilities in particular.…”
Section: Discussionmentioning
confidence: 99%